2022
DOI: 10.3390/rs14143401
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Detailed Wetland Inventory with Sentinel-2 Time-Series Data and Google Earth Engine in the Prairie Pothole Region of Canada

Abstract: Wetlands in the Prairie Pothole Region (PPR) of Canada and the United States represent a unique mapping challenge. They are dynamic both seasonally and year-to-year, are very small, and frequently altered by human activity. Many efforts have been made to estimate the loss of these important habitats but a high-quality inventory of pothole wetlands is needed for data-driven conservation and management of these resources. Typical landcover classifications using one or two image dates from optical or Synthetic Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Similar outcomes have also been evidenced for seasonal waters (Bangira et al, 2019; Huang et al, 2018). For small water bodies, recent studies have reported high accuracy in surface water occurrence and extent for sizes ranging from 0.5 ha (Wang et al, 2022) up to 5 ha (DeLancey et al, 2022; Peña-Luque et al, 2021). To date, there is a scarcity of research specifically addressing very small water bodies (<0.5 ha), and the few existing studies focusing on this range of sizes (0-0.5 ha) have consistently demonstrated suboptimal performance, especially when employing publicly available EOS data (Cordeiro et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similar outcomes have also been evidenced for seasonal waters (Bangira et al, 2019; Huang et al, 2018). For small water bodies, recent studies have reported high accuracy in surface water occurrence and extent for sizes ranging from 0.5 ha (Wang et al, 2022) up to 5 ha (DeLancey et al, 2022; Peña-Luque et al, 2021). To date, there is a scarcity of research specifically addressing very small water bodies (<0.5 ha), and the few existing studies focusing on this range of sizes (0-0.5 ha) have consistently demonstrated suboptimal performance, especially when employing publicly available EOS data (Cordeiro et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the table reveals predominant transitions into wetland from barren and vegetated surfaces, highlighting wetland expansion mainly occurring in formerly non-vegetated bare lands. It also quantifies the minor exchanges between wetlands and built-up impervious surfaces in the landscape surrounding Khinjhir Lake [75,76].…”
Section: Transition Of Wetlandmentioning
confidence: 99%
“…Additionally, Fekri et al [39] developed a RF algorithm and an automatic change detection method in GEE to map and identify changes in the International Shadegan Wetland (ISW) areas in southwestern Iran from 2018 to 2021 using a combination of Sentinel-1 and Sentinel-2 data. Finally, DeLancey et al [40] used Sentinel-2 imagery from 2017 to 2020 in GEE to monitor the seasonal flooding dynamics of wetlands in a prairie pothole wetland landscape in Alberta, Canada.…”
Section: Introductionmentioning
confidence: 99%